2020
DOI: 10.1101/2020.04.17.044792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

c-Fos-MMP-9 pathway in central amygdala mediates approach motivation but not reward consumption

Abstract: Although impairments of motivational and consummatory aspects of reward behavior are core symptoms of several psychiatric disorders, the underlying neural and molecular mechanisms remain poorly understood. Here we report that blocking either c-Fos or matrix metalloproteinase 9 in the central amygdala disrupts approach motivation and appetitive discrimination learning, but not reward consumption. Further, we show that manipulation of c-Fos-MMP-9 pathway does not affect aversive motivation and learning. These fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In line with a rescue of impaired LTP in Fmr1 KOs, it was also reported that an MMP-9 inhibitor (GM6001) increased maturation of dendritic spines and improved LTP in brain slices obtained from rats overexpressing MMP-9, animals with significant deficits in the LTP [ 78 ]. Interestingly, we have also found that a very slight increase in MMP-9 activity in the CeA of WTs reinforces motivation for sugar water ([ 79 ], in review ). A similar motivational boost was also reported in the alcohol-consuming MMP-9 knock-out animals with CeA-restricted exogenous expression of the enzyme [ 80 ], which further solidifies the notion that a fine balance of the enzyme activity is needed for the correct reward processing.…”
Section: Discussionmentioning
confidence: 87%
“…In line with a rescue of impaired LTP in Fmr1 KOs, it was also reported that an MMP-9 inhibitor (GM6001) increased maturation of dendritic spines and improved LTP in brain slices obtained from rats overexpressing MMP-9, animals with significant deficits in the LTP [ 78 ]. Interestingly, we have also found that a very slight increase in MMP-9 activity in the CeA of WTs reinforces motivation for sugar water ([ 79 ], in review ). A similar motivational boost was also reported in the alcohol-consuming MMP-9 knock-out animals with CeA-restricted exogenous expression of the enzyme [ 80 ], which further solidifies the notion that a fine balance of the enzyme activity is needed for the correct reward processing.…”
Section: Discussionmentioning
confidence: 87%